1990
DOI: 10.2307/4002357
|View full text |Cite
|
Sign up to set email alerts
|

Botanical Composition of Goat Diets in Thinned and Cleared Deciduous Woodland in Northeastern Brazil

Abstract: Clearing and thinning of caatinga vegetation in northeastern Brazil are viewed as methods of optimizing forage and wood production. Our study compared the botanical composition of goat diets relative to forage availability in undisturbed, cleared and 2 levels of thinned (25% and 55% canopy cover) stands of tropical woodland. Clearing and thinning of caatinga vegetation resulted in higher amounts of available forage through the wet season and up to the time of leaf fall. At the end of the growing season, availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…Reduction of the woody component resulted in an increase of the standing herbaceous vegetation. This was expected and demonstrated in similar previous studies (Kirmse et al, 1987b;Schacht and Malechek, 1990;Papanastasis and Liacos, 1991).…”
Section: Forage Biomasssupporting
confidence: 73%
“…Reduction of the woody component resulted in an increase of the standing herbaceous vegetation. This was expected and demonstrated in similar previous studies (Kirmse et al, 1987b;Schacht and Malechek, 1990;Papanastasis and Liacos, 1991).…”
Section: Forage Biomasssupporting
confidence: 73%
“…Goats have been domesticated worldwide, including areas with harsh environmental conditions. Studies in various parts of the world have shown their grazing selectivity (Malechek & Leinweber 1972;Provenza & Malechek 1984;Schacht & Malechek 1990). It is known that goat browsing results in changes of plant species composition; some species decline, whereas those avoided by goats increase (Riggs & Urness 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The goats are opportunistic foragers and can maintain a high quality diet under diverse conditions (Schacht and Malechek, 1990;Elamirez et al, 199Oa). As a result goats have acquired a reputation for survivability on harsh, degraded rangelands (Devendra, 1978).…”
Section: Introduction Indices Ranges Mkxicomentioning
confidence: 98%